2003
DOI: 10.1291/hypres.26.881
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Polymorphism of the Angiotensin-Converting Enzyme Gene and the Response to Angiotensin-Converting Enzyme Inhibition in Hypertensive Patients

Abstract: The aim of this study was to investigate the relationship between polymorphism of the angiotensin-converting enzyme (ACE) gene and the blood pressure response to ACE inhibition in a hypertensive cohort. Imidapril (5--10 mg/day) or benazepril (10--20 mg/day) was administered for 6 weeks to 517 essential hyperten-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
(34 reference statements)
0
13
0
3
Order By: Relevance
“…These endpoints have ranged from improvement in measured hemodynamics to reduction in proteinuria to BP response. However, significant conflicting data have since been reported that reveal no association between rs1799752 and ACEI or ARB BP response 17,[33][34][35][36][37][38][39] . Although evidence does not support the use of rs1799752 as a predictor of ACEI or ARB response, a few studies suggest this SNP may remain a predictor of diuretic response [40][41][42] .…”
Section: Candidate Pharmacodynamic Polymorphisms Of the Renin-angiotementioning
confidence: 99%
“…These endpoints have ranged from improvement in measured hemodynamics to reduction in proteinuria to BP response. However, significant conflicting data have since been reported that reveal no association between rs1799752 and ACEI or ARB BP response 17,[33][34][35][36][37][38][39] . Although evidence does not support the use of rs1799752 as a predictor of ACEI or ARB response, a few studies suggest this SNP may remain a predictor of diuretic response [40][41][42] .…”
Section: Candidate Pharmacodynamic Polymorphisms Of the Renin-angiotementioning
confidence: 99%
“…The association between ACE I/D polymorphism and hypertension 10,24 has been reported, with high morbidity rate for hypertensives and diabetics, although studies conducted with Caucasian populations have not detected a more impacting effect of that gene in hypertensives 18,[38][39][40][41][42] . A study where Blood Pressure Ambulatory Monitoring (ABPM) was used, BP and pressure load were related to ACE I/D polymorphism 43 .…”
Section: Hypertension and Renin-angiotensin System Polymorphismsmentioning
confidence: 99%
“…It has been reported that the ACE I/D polymorphism may influence the ability of imidapril to prevent restenosis after percutaneous transluminal coronary angioplasty (16). However, the responsiveness to imidapril showed no association with the ACE I/D genotype (17), and the genes and the genotypes that are associated with the response to this drug remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%